Integrating Education Character Into Reading Materials In Tarbiyah And Teachers’ Training Faculty Of Iain Ponorogo - Nurul Khasanah (Kodifikasia: Jurnal Penelitian Islam, 2018)
This research and development (RnD) aimed at developing reading materials in basic reading course for second semester students of English Department of IAIN Ponorogo. This study used ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model proposed by Florida State University. To collect the data, questionnaire, observation sheets, interview, and test applied. The need analysis conducted by distributing questionnaire to the students and delivering interview to the head of the English Department. The result of need analysis indicates that the students and the head of English department are agreed to integrate character education into reading materials. The education character that are integrated in the reading materials are religiosity, honesty, tolerance, discipline, creativity, curiosity, and fond of reading.